Description of three new species of genus Vacrothele (Araneae, Mygalomorphae, Macrothelidae) from China with notes on two taxonomic amendments - Yu-Lin Zheng; Yu Zhao; Zi-Zhong Yang (European Journal of Taxonomy)
Three new species of the genus Vacrothele Tang & Yang, 2022 are described in detail from China: Vacrothele fuyuanensis sp. nov., Vacrothele jiangkouensis sp. nov. and Vacrothele baiseensis sp. nov. Two described species of the Macrothele are transferred to the genus, i.e., Vacrothele emei (Lin & Li, 2021) comb. nov. and Vacrothele taiwanensis (Shimojana & Haupt, 1998) comb. nov. A key to species of Vacrothele and a geographic distribution map are given.